2017
DOI: 10.5267/j.ijiec.2017.3.001
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of surface roughness and productivity thru RSM in face milling of AISI 1040 steel using coated carbide inserts

Abstract: The aim of this study is to evaluate the impact of factors such as cutting speed, feed rate, and depth of cut on surface roughness and Material Removed Rate (MRR) when machining in dry face milling AISI 1040 steel with coated carbide inserts GC1030 using the response surface methodology (RSM). For this purpose, a number of machining experiments based on statistical three-factor and three-level factorial experiment designs, completed (L27) with a statistical analysis of variance (ANOVA), were performed in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The desirability function method has been used in numerous research studies [21][22][23][24][25] in order to optimize a manufacturing process pertaining to turning, milling or various other operations [26,27]. This approach allows the combination of multiple responses into a single function (the Desirability Function or DF) through the choice of a value comprised between zero and one (least to most desirable, respectively).…”
Section: Desirability Function (Df) Application and Optimizationmentioning
confidence: 99%
“…The desirability function method has been used in numerous research studies [21][22][23][24][25] in order to optimize a manufacturing process pertaining to turning, milling or various other operations [26,27]. This approach allows the combination of multiple responses into a single function (the Desirability Function or DF) through the choice of a value comprised between zero and one (least to most desirable, respectively).…”
Section: Desirability Function (Df) Application and Optimizationmentioning
confidence: 99%
“…For this purpose, a number of machining experiments based on statistical three factor and three level factorial experiment designs, completed (L27) with a statistical analysis of variance (ANOVA), were performed in order to develop mathematical models and to identify the significant factors of these technological parameters. It was determined that cutting speed is the most important parameter affecting the surface roughness [33]. In this study, it is aimed at determining suitable cutting tools and cutting parameters for surface roughness and cutting tool wear in face milling Custom 450 stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that feed was a crucial factor on surface roughness. Fnides et al [8] used RSM and DFA based optimizations to find the optimum cutting conditions of minimum surface roughness and maximum material removal rate in face milling of AISI 1040 steel. Palanisamy et al [9] experimented for milling of T6-6061 aluminium alloy to optimize cutting conditions using RSM.…”
Section: Introductionmentioning
confidence: 99%